Panel Estimation of the Impact of Foreign Banks Presence on Selected Banking Indicators in Macedonia - Ana Mitreska; Sultanija Bojcheva-Terzijan (National Bank of the Republic of Macedonia, 2017)
The latest global financial and economic crisis reignited the debate on the costs and benefits of foreign bank presence. While discussions on the optimal financing model of foreign owned banks are ongoing, the consensus on the benefits of foreign banks presence is not a matter of dispute. Given the large and enduring foreign presence in the Macedonian banking system, we try to empirically test some of the traditional channels of the foreign banks impact on the banking system behaviour. We employ panel estimation method with a pooled mean group estimator. The results do confirm the thesis that foreign banks presence in Macedonia supports the competition in the banking system in the long run, visible through the narrowing of some of the profitability indicators. Yet, what they also suggest is that it happens via rise in the operational costs - commonly result of the new investments of foreign owners in knowledge and technology. On the other hand, the interest income component is positively affected by the change in the foreign banks presence. The findings suggest that the observed trend of falling share of interest income in interest earning assets and falling operational costs, on a long run can be explained by other fundamental factors, rather than the actual dynamics of foreign bank presence. The availability of bank funding is one of those fundamentals, which can explain the adjustment in the interest income, in particular.
Keywords: C23; F21; G21; 330; foreign banks presence; banking indicators; international investment; panel estimates; pooled mean group estimator